Qual é a tua, oh Lampião? Tensionamentos em um jornal editado na e pela Esquina - Cruz, João Lúcio Mariano (2019)
Our study aims to analyse the tensioning between women, black people and homossexuals in the Lampião da Esquina Newspaper publications. This alternative newspaper circulated from 1978 to 1981, conducted by gay men that proposed dialogues between lesbians, transvestite, black people and feminists. We choose the perspectives from dialogicity and intersectionality as theoretical possibilities to view the conflicts, in the search for emancipation, noticed in the pages of the newspaper from the Esquina publishing house. We resort to reading these past, to build up relations with the meanings from nowadays, asking to the future the matter of the symbolic production of journalism in construcion of senses and their dynamics with the power. In methodological terms, we use the interpretative analysis in convergence with discourse analysis for a careful reading of the newspaper. The editions we use here enable us to view that the diferent axes of social diferenciation reveal the complexity of identities; the relations between diferent groups is stressed by conflicts engender by different points of view, experiences and specificities from structural demands and opressions, and that Lampião da Esquina was, in the same time, a tensioning platform and experimentation tool of citizenship construction.